O poder da Igreja Universal do Reino de Deus: um estudo sobre a inserção sociopolítica dos neopentecostais no Brasil e suas implicações para a democracia (1999-2009) - Gomes, Geórgia Daphne Sobreira (2010)
The present study has as deep the sprouting of new religious movements in world-wide level in the present time, phenomenon narrowly tied with the new contours that the religion and the religiously have in the culture crisis of modernity, marked under the sign of globalization in different levels. From the reflection on this new paradigm, come the analysis of the avance of pentecostalism in Latin America, particular in Brazil, basecally on its spectacular ascension on the catholic tradition in the continent. In this context, is situated the sprouting of a diversity of pentecostalism denominations, the neopentecostalism, whose performance is different than the historical evangelism and inaugurates new operational forms, reproducing the capitalist culture in its current period of training. This study approaches also it magnifying in its activities, especially in the politician sector in the last ten years, on which they come acting in the defense of its interests. In Brazil, the Universal Church of the Kingdom of God - IURD is detached in this direction. With focus in its politician-partisan performance and on the results of a empiricist research that the study analyzes which the implications of the insertion of the IURD in the politics and brazilian democracy